Investigation of nickel aluminium bronze (nab) metals cast and its properties - Mohd Nasuha, Ab Halim (2023)
There are three major types of aluminium bronze which is Binary Aluminium Bronze, complex nickel aluminium bronze and silicon aluminium bronze which start from a small addition of aluminium into copper which started from the discovered previous researcher that resulting an increase of hardness of copper alloy without affecting its malleability. Producing NAB alloy can lead to the absorption of gaseous such as oxygen and nitrogen during solidification stage and create a defect on properties and physical to NAB alloy. Another challenge is also present when a product has a complex shape resulting in a variety of cooling rates during solidification and resulting to non-uniformity of the microstructure of the product. This study inspects the effect of thickness during the metal casting process on the microstructure of copper alloy products toward to its properties, microstructure and corrosion. The copper alloy used in this project is Nickel Aluminium Bronze (NAB) alloy, which consists of elements such as Cu, Al, Fe, and Mn. From the previous literature, adjustment of NAB alloy microstructure has been proven to improve the quality toward to properties in automotive and marine applications. The sample is shaped like a connecting rod and fabricated using the sand casting technique. The composition was prepared according to the ASTM B148 UNS95800 standards and melted using an induction furnace at 1100˚C, then poured into a sand casting mould with a 1.1% degassing agent. The sample solidified at ambient temperatures, and then the specimen from the NAB alloy sample was cut into 3 sections according to its thickness. The study is continued by investigating the properties, microstructure, dendrite structure, and corrosion by optical microscope, SEM, FESEM, EDS, and XRD. Based on the results, the microstructure morphology shows a quantity of DAS and SDAS per unit area becomes higher due to a longer solidification time. Casting cavity’s temperature is higher as the thickness increases due to higher casting volume in the melting state. The size and dimension are affected as well. This eventually results in better properties, such as higher hardness and good corrosion resistance. The fracture surface also reveals intergranular fracture between the dendritic structure and grain boundaries. Later, the specimens were immersed in seawater in the corrosion resistance study. Changes in the specimen mass, pH and TDS values of the seawater used were measured. The data analysis revealed that the specimens were not fully corroded for the immersion period, as there were phase variations in the specimen microstructure. The pH and TDS values show changes, but these changes are minimal comparatively. The conclusion of research shown that effect of degassing on different cavity thickness of NAB mechanical properties on thicker which is holding longer latent heat and slower cooling rate that produces part produces lower microhardness, larger grain size, larger DAS and SDAS and possibility to have a higher corrosion rate compared to thinner part. Based on this research, NAB alloy are very suitable to be use in maritime application with its lower corrosion rate and improved mechanical properties.